Diffused suberitrodermic psoriasis induced by infliximab - V. Bruzzese (PAGEPress Publications, 2011)
The case of a young male is described, affected by Crohn disease with reactive Spondoloarthritis essay with Infliximab to the dose of 3 mg/kgs. After 15 days from the 3° infusion, the patient developed a first psoriasic eruption to the palm of the hands and the plant of the feet, for which was begun topical therapy with cortisone. After an initial improvement, the patient introduced a diffusion of the psoriasic eruption to the whole trunk and the limbs with a suberitrodermic aspect. The possible pathogenesis of this paradoxical effect of the anti-TNF is considered. Also being still partly the causes, is important the inhibition of the TNF-alpha with consequent expansion of the INF-alpha, in tum potential inductor of psoriasis.